Gene × Environment Interaction in Developmental Disorders: Where Do We Stand and What’s Next? - Esposito, Gianluca; Azhari, Atiqah; Borelli, Jessica L. (Frontiers in Psychology, 2018)
Although the field of psychiatry has witnessed the proliferation of studies on Gene x Environment (GxE) interactions, still limited is the knowledge we possess of GxE interactions regarding developmental disorders. In this perspective paper, we discuss why GxE interaction studies are needed to broaden our knowledge of developmental disorders. We also discuss the different roles of hazardous versus self-generated environmental factors and how these types of factors may differentially engage with an individual’s genetic background in predicting a resulting phenotype. Then, we present exemplar studies that highlight the role of GxE in predicting atypical developmental trajectories as well as provide insight regarding treatment outcomes. Supported by these examples, we explicate the need to move beyond merely examining statistical interactions between genes and the environment, and to investigate specific genetic susceptibility and environmental contexts that drive developmental disorders. We propose that further parsing of genetic and environmental components is required to fully understand the unique contribution of each factor to the etiology of developmental disorders. Finally, with a greater appreciation of the complexities of GxE interaction, this discussion will converge upon the potential implications for clinical and translational research.